(untitled) (Cadernos de Ética e Filosofia Política, 2019)
This paper intends to investigate the development of the "ethical spirit" in Hegel's Jena writings. Based on Hegel's notion of consciousness as "middle" (Mitte), discussed in the philosophy of the spirit (1803/04), the task is firstly to analyze the methodological conditions for the foundation of ethical life's unfolding on a consciousness theory. Then the aim is to consider the development of ethical spirit as a movement in which its intersubjective constitution and the relation of the individual to the ethical substance are articulated. Finally, starting with Hegel's conception of practical reason as ethical life, delineated in the Phenomenology, I argue that, besides the connection between consciousness theory and conceptual development of ethical life, Hegel maintained that two-fold constitution of the ethical spirit.